Serum Level of Vitamin D and Febrile Seizure? A Clinical Study - Heydarian, Farhad; Bakhtiari, Elham; Golmakani, Hasan; Fakhr-Ghasemi, Neda; Heidarian, Mohammad (Iranian Journal of Child Neurology, 2020)
Objective: To evaluate the serum level of vitamin D in children aged six to 60 months with febrile seizure and febrile children without the seizure Materials & Methods Febrile children aged six to 60 months with or without seizure were studied. Demographic characteristics, serum level of vitamin D, and other laboratory findings were recorded. Results Among the 104 children, 51 patients had fever without a seizure and 53 patients had a febrile seizure. The mean subjects’ age was significantly more in the febrile seizure group compared to the without seizure group (16.26 ± 11.87 versus 26.36 ± 14.11 months, p = 0.001). The mean serum level of vitamin D in the with and withouts eizure groups was 41.92 ± 22.42 and 48.41 ± 15.25 microgram perd eciliter, respectively (p = 0.08). There was no significant correlation between serum level of vitamin D and seizure occurrence (p = 0.07).The mean serum sodium and potassium levels, and platelet count were significantly lower in the febrile seizure group compared to the without seizure group (p < 0.05). There were no significant differences between the two groups regarding hemoglobin, blood sugar, creatinine, blood urea nitrogen, calcium, alkaline phosphatase levels, and white blood cell count (p > 0.05). Conclusion The serum level of vitamin D in febrile children with or without seizure was normal. The serum level of vitamin D was lower inp atients with the seizure but not statistically significant. More clinical studies are needed to evaluate the relationship between febrile seizurea nd the serum level of vitamin D.